Pengembangan Media Pembelajaran Interaktif Berbasis Smart Apps Creator Mata Pelajaran IPAS Kelas IV SDN 14 Pontianak Selatan - Ririn, Elisia Rania; Salimi, Asmayani; Ghasya, Dyoty Aulia Vilda (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This study aims to produce a product in the form of interactive learning media based on Smart Apps Creator for the IPAS subject that is deemed suitable for use. The Research and Development (R&D) method is employed, adapting the Borg & Gall development method, which includes only 7 stages: research and data collection, planning, initial product development, initial field testing, main product revision, field testing, and operational product revision. This research involves both qualitative and quantitative approaches. Data collection methods include interviews, documentation, validator validation questionnaires, and questionnaires during field testing. The results indicate that during the development process of interactive learning media based on Smart Apps Creator, these seven stages were successfully executed. The language aspect's feasibility, with the highest percentage value at 83%, falls into the